PENINGKATAN HASIL BELAJAR MATEMATIKA MELALUI MODEL TEAMS GAMES TOURNAMENT (TGT) BERBANTUAN MEDIA ULAR TANGGA PADA SISWA KELAS IV SD - Khairunnisa, Elvira; Yumna; Dahliana, Dina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to improve students’ mathematics learning outcomes of fourth-grade students at SDN 01 Paninjauan, where only 43% of students achieved the Learning Objective Achievement Criteria (KKTP). This study aimed to improve students' mathematics learning outcomes through the application of the Teams Games Tournament (TGT) model assisted by a snake and ladder game. The research method used was collaborative classroom action research (PTK) referring to the Kemmis & McTaggart model, which was carried out in two cycles, with 7 fourth-grade students as the research subjects. Data collection techniques in this study included tests, observations, documentation, and interviews. The results showed a significant increase in the average cognitive learning outcomes, from 64.28 in the pre-cycle to 72.85 in cycle I, and reaching 85.71 in cycle II. Classical learning completeness also increased from 43% in the pre-cycle to 57% in cycle I, and reached 86% at the end of cycle II. In addition, student activity and learning management by teachers also improved with a “Good” rating. Therefore, it can be concluded that the application of the TGT model assisted by the snake and ladder media is effective in improving the mathematics learning outcomes of fourth-grade students at SDN 01 Paninjauan. This study contributes to the development of interactive learning strategies in elementary education.